2018
DOI: 10.1039/c8cp01364k
|View full text |Cite
|
Sign up to set email alerts
|

Hittorf's violet phosphorene as a promising candidate for optoelectronic and photocatalytic applications: first-principles characterization

Abstract: Utilizing density functional theory, we investigate the structural stabilities, electronic structures, and optical properties of monolayer violet phosphorene, i.e., Hittorfene, under an external vertical electric field and upon in-layer biaxial strain control. We find that compared with monolayer black phosphorene, monolayer violet phosphorene has a significantly larger direct band gap of 2.50 eV, and it is sensitive to an external vertical electric field, under which it undergoes an intriguing direct-indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 33 publications
2
23
0
1
Order By: Relevance
“…Interestingly, the calculated energy gap found for single-layer Hittorf's P (1.70eV) is much wider compared to its black counterpart (0.89eV). These resulting values are quite close to those reported in literature 46,54 , as described in Table S2 reported in Section 1 of Supplementary Information. The direct character of the band gap has been double-checked using the Grimme D3 version and we found no changes.…”
Section: Table 4 Pbe+d2 Optimized Unit Cell Lattice Vectors Of Hittorf's Phosphorus Compared Withsupporting
confidence: 90%
“…Interestingly, the calculated energy gap found for single-layer Hittorf's P (1.70eV) is much wider compared to its black counterpart (0.89eV). These resulting values are quite close to those reported in literature 46,54 , as described in Table S2 reported in Section 1 of Supplementary Information. The direct character of the band gap has been double-checked using the Grimme D3 version and we found no changes.…”
Section: Table 4 Pbe+d2 Optimized Unit Cell Lattice Vectors Of Hittorf's Phosphorus Compared Withsupporting
confidence: 90%
“…[32][33][34][35] Following the fact nding journey, many other allotropes/ polytypes of phosphorene viz., red, black, violet, green phosphorene have been realized [36][37][38][39] and some of them have been explored for water splitting application. [40][41][42][43] More recently, a new member of phosphorene polytype was realized through the synthesis of mono-layered honeycomb buckled bluephosphorene (B-phosphorene) on an Au (111) sheet using a molecular beam epitaxial method with black-phosphorous as precursor. 44 It has been reported that a specic dislocation in black phosphorene induces a new structure with zigzag puckering, called B-phosphorene with a characteristic tunable bandgap upto 2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…It was even debated as to whether violet phosphorus was even a stable allotrope or a metastable intermediate from red to black phosphorus. [10] Violet phosphorene, a promising semiconducting 2D material for photonic and electronic applications, [11] stays unexplored owing to the uncertainty of its bulk structures. The properties of both bulk and layered violet phosphorus are unexplored, which hinders their further applications.…”
mentioning
confidence: 99%